Maternal and fetal outcomes in 151 cases of thrombocytopenia in pregnancy - Ibeh, Chinwe Oluchi-Amaka; Guo, Feng; Yang, Xiuhua (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThrombocytopenia during pregnancy is one of the important causes of maternal and perinatal mortality. This study aims to retrospectively analyze the clinical data of 151 pregnant patients with thrombocytopenia, in order to help obstetricians better understand the etiology, related risk factors and maternal and fetal outcomes of this disease.MethodsA total of 151 cases of pregnant women with thrombocytopenia were collected. According to the cause of thrombocytopenia, patients were divided into gestational thrombocytopenia (GT) group, hypertensive disorders in pregnancy (HDP) group, immune thrombocytopenia (ITP) group and the other group. According to the degree of thrombocytopenia, patients were divided into mild group, moderate group and severe group. According to different grouping criteria, the clinical characteristics, delivery outcomes and delivery modes, maternal treatments during pregnancy, maternal laboratory indexes, and neonatal birth conditions were compared.ResultsAmong the 151 patients, the GT group had the largest proportion. Moreover, the ITP group had a higher proportion of skin and mucous membrane bleeding during pregnancy, the smallest gestational age at first diagnosis and the lowest platelet count at first diagnosis. The treatment effect of glucocorticoids alone in the ITP group was not good. The HDP group had a higher neonatal intensive care unit (NICU) transfer rate and the lowest birth weight in newborns. In terms of severity, majority of the patients were in the mild group. The parameters of thromboelastography (TEG) were related to the pre-delivery platelet count of patients in the moderate and severe groups, but not in the mild group.ConclusionIn conclusion, ITP is associated with more severe thrombocytopenia and bleeding, often presenting in the early stage of pregnancy. In the treatment of ITP, the combined use of glucocorticoids and platelet transfusion is recommended. TEG parameter analysis suggests that patients in the moderate and severe groups may have changes in the blood coagulation and fibrinolysis systems. More attention should be paid to the monitoring of the newborns delivered by HDP patients.